Desecration of the Earthly Paradise: An Ecocritical Reading of Mirza Waheed’s Novel The Book of Gold Leaves - Muhammad Shoaib (Journal of Research in Humanities, 2019)
Kashmir, with its unique blend of picturesque landscape, perennial fresh water streams and lakes, lush-green vegetation, snowcapped peaks, variety of birds, rare animals and various seasons with changing hues, is one of the most environmentally vibrant areas in South Asia. Traditionally known as the paradise on the earth, the valley is currently sandwiched between the geopolitical ambitions of India and Pakistan, and host to the worst political crisis in the region. It is plagued with militarism, violence, encounters, curfews, atrocities, and controversies. This research paper on Kashmiri novelist Mirza Waheed’s work The Book of Gold Leaves (TBGL) (2014) links the ecological crisis in the valley to the unending cycle of violence and terror. Violence has created an environment of fear in the valley which overshadows the beauty of the land. Tourism to Kashmir has dwindled almost to non-existence. Landscape, forests, water bodies, birds and animals face an existential threat at the hands of the ecocidal forces which are proactive in the valley. Historically, there has been a dearth of authentic voices from the Indian part of Kashmir to record the conflict, fear and ecological crisis emanating from the presence of the Indian military, armed resistance and negligence. But the current writers from Kashmir are bent on emphasizing the gravity of the ecological situation. Keeping in view all this and partially drawing on ecocritical and ecofeminist strands of ecology, this paper explores the strategic use of ecological trope on the part of Mirza Waheed to highlight the plight of Kashmir along with its flora and fauna.